Homo educandus : why our school system is broken and what we can do about it - Bransen, Jan, 1958- (Radboud University Press, 2021)
Linnaeus, the Swedish taxonomist, was wrong when he named our species Homo sapiens, i.e. wise man. We are not. We do too many senseless, destructive and irresponsible things to deserve that label. Actually, we need to be educated. Fortunately, we can be educated. We can transform ourselves. We are Homo educandus. Sadly, our current school system is broken. In fact, it does not support education. It deforms. This is what Jan Bransen claims in this book. He convincingly argues that our current school system is based on incoherent ideas, among which the notions that people need to study for years on end before they are ready to take part in our society, or that students learn because teachers teach. We can do better than that. In the second part of the book, Bransen points out that we have reasons to be confident and enthusiastic. We can improve our education system. Applying a dramaturgical analysis of human action, Bransen explains what socialization should look like in primary education, how our personal development can be supported in secondary education and how qualification can be organized in dual tracks in higher education, integrating learning, working and living over our course of life.